Modeling and Simulation of Non-Grid-Connected Wind Energy Conversion System (International Journal of Engineering and Computer Science, 2017)
Method for wind turbine controller design and test in laboratory still remains a problem. This paper presents a real time simulator of non-grid-connected wind energy conversion system suitable for controller design and test. The simulation model, which is composed of a fixed-pitch wind turbine, a permanent magnet synchronous generator with PWM voltage source vector control and DC-DC converter with peak current control, is especially suitable for electrochemical industries. High energy efficiency can be achieved by adjusting the rotor speed according to the wind speed. Simulation results show the validity of system modeling and control strategy.